Relationship between job success and career adaptability in the vocational trajectories of the LCI VERITAS graduated community (Revista Electrónica Calidad en la Educación Superior, 2025)
The article examines the relationship between career adaptability and job success among graduates of the Universidad LCI Veritas during the 2017-2022 period based on their career trajectories. A quantitative approach was used, with a non-experimental, transactional design and a correlational scope. A survey was administered to a sample of 250 individuals, which was probabilistic and stratified by career. The main finding was a significant and positive correlation between the two variables [r=0.455, n=250, p
Keywords: job satisfaction; career orientation; career development; transition to active life and graduate